Digital system clocking : high performance and low-power aspects - Oklobdzija, Vojin G.; Stojanovic, Vladlmlr M.; Markovic, Dejan M.; Nedovic, Nikola M. (IEEE ; Wiley-Interscience, 2003)
Provides the only up-to-date source on the most recent advances in this often complex and fascinating topic. . The only book to be entirely devoted to clocking. Clocking has become one of the most important topics in the field of digital system design. A "must have" book for advanced circuit engineers